Implementasi Kegiatan Sinau Bareng Sebagai Wujud Pendalaman Kreatifitas Di Kelurahan Wonorejo - Arif Noer Vikri; Divva Grizelda Meisari; Anindya Benita Fawwaz Hidayat; Muhammad David Khalik; Della Ayu Minarni; Virginia Mandasari (Universitas 17 Agustus 1945 Semarang, 2023)
The Sinau Bareng Program, which is a program of the Surabaya City Education Department, is held every Monday and Saturday, starting at 18.00 to 20.00 WIB. This program is usually attended by children from various levels of education starting from kindergarten, elementary school, middle school, to high school and is free of charge. The method used is to conduct study groups. This activity was held with the aim of helping and accompanying children in learning and carrying out their assignments given at school, and to provide a forum for children to be able to carry out positive, creative, and productive activities. The students who attend this program usually want to study their subjects such as Mathematics, Indonesian, English, and so on. Not only that, in this sinau together program, the Bina Desa Group also held fun